Beyond (COVID-19) lockdown: faculty experiences in the post-pandemic academic landscape - Dewangan, Roshan Lal; Longkumer, Imlisongla; Gupta, Shashidhar; Pathak, Smriti (Frontiers in Education, 2024)
Background: This study investigates the nuanced experiences of faculty members in higher education institutions during and after the COVID-19 pandemic. Focusing on family-work conflict, job satisfaction, and personal wellbeing, the research aims to provide comprehensive insights into the challenges and adaptations encountered by faculty members amidst unprecedented disruptions. Method: A mixed-method approach was employed, encompassing both quantitative and qualitative measures. The quantitative facet involved 82 participants who responded surveys distributed to faculty members across diverse regions of India. Concurrently, qualitative data were collected through interviews with 30 faculty members in three states. The quantitative study utilized standardized tools, while the qualitative inquiry followed a semi-structured interview schedule. Result: Quantitative findings revealed a significant upswing in job satisfaction after institutional reopening compared to the lockdown period. However, no significant differences were observed concerning work-family conflict and personal wellbeing. Notably, faculty members reported heightened work-family and family-work interference compared to national statistics. Qualitative responses highlight a notable shift in teaching methodologies, incorporating multimedia and online tools. Faculty members exhibited mixed sentiments about returning to the office, expressed a deepened appreciation for social relationships post-reopening, and emphasized the positive impact of institutional hygiene protocols. Conclusion: This study offers crucial insights into the multifaceted experiences of faculty members in higher institutions during the COVID-19 lockdown and subsequent reopening. The research contributes valuable perspectives to the evolving discourse on post-pandemic academia, providing a foundation for further exploration and understanding of the challenges and opportunities faced by faculty members in the changing scenario of higher education.